Bergapten induces G1 arrest and pro‐apoptotic cascade in colorectal cancer cells associating with p53/p21/PTEN axis. Issue 3 (21st December 2018) - Lin, Ching‐Pin; Lin, Chun‐Shiang; Lin, Hui‐Han; Li, Kuan‐Te; Kao, Shao‐Hsuan; Tsao, Shih‐Ming
Abstract: Bergapten is a natural compound and has potent anticancer activities. In this study, we explored the cytotoxicity of bergapten on colorectal cancer (CRC) cell DLD‐1 and LoVo and its underlying mechanisms. We observed that bergapten (30 and 50 μM) decreased the viability of the CRC cells and induced the G0/G1 and sub‐G1 phase arrest. Furthermore, immunoblotting results indicated that bergapten increased p53, phospho‐p53(Ser‐46), p21, PUMA, Bax, PTEN, and the caspase‐9 and caspase‐3 cleavage, but decreased cyclin E, CDK2, and phosphor‐AKT(Ser‐473) in the CRC cells. Inhibition of p53 by pifithrin‐α reversed the bergapten‐induced p53‐mediated apoptotic cascade and restored the survival signaling and cell viability. Collectively, our findings reveal that bergapten decrease the cell viability and induce cell cycle arrest in the CRC cells, which may be attributed to p53‐mediated apoptotic cascade, upregulation of p21 and PTEN, and inhibition of AKT.